1994
DOI: 10.2183/pjab.70.127
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation of Phytoplasma Isolates Determined by a DNA Heteroduplex Mobility Assay.

Abstract: Abstract:Regions representing about 80% of the 16S rDNA sequences of nine phytoplasma isolates were amplified by polymerase chain reaction (PCR). These partial 16S rDNA sequences amplified from the various phytoplasmas were used in DNA heteroduplex mobility assays (HMA). Based on DNA distances derived from HMA analysis, the nine phytoplasma isolates may be classified into four distinct groups: group I, paulownia witches'-broom (China), potato purple top (France); group II, tomato stolbur (France); group III, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…HMA has a higher sensitivity for detecting DNA mutations than any other technique currently available, except exhaustive DNA sequencing (Delwart et al ., 1993, 1994; Wang & Hiruki, 1999, 2000a, 2001b). In phytoplasma studies, HMA has been suggested as an accurate means for identifying and classifying phytoplasmas, while other methods such as RFLP do not readily differentiate very closely related phytoplasmas at the subgroup level (Zhong & Hiruki, 1994; Ceranic‐Zagorac & Hiruki, 1996; Wang & Hiruki, 1999, 2000a, 2001a,b).…”
Section: Introductionmentioning
confidence: 99%
“…HMA has a higher sensitivity for detecting DNA mutations than any other technique currently available, except exhaustive DNA sequencing (Delwart et al ., 1993, 1994; Wang & Hiruki, 1999, 2000a, 2001b). In phytoplasma studies, HMA has been suggested as an accurate means for identifying and classifying phytoplasmas, while other methods such as RFLP do not readily differentiate very closely related phytoplasmas at the subgroup level (Zhong & Hiruki, 1994; Ceranic‐Zagorac & Hiruki, 1996; Wang & Hiruki, 1999, 2000a, 2001a,b).…”
Section: Introductionmentioning
confidence: 99%
“…However, the technique of RFLP analysis does not necessarily detect all subtle DNA‐based differences among strains, and does not give a reliable estimation of phylogenetic distance (Seemüller et al ., 1998), while DNA sequencing is expensive and time‐consuming when several samples must be analysed. In contrast, heteroduplex mobility assay (HMA) provides a comparative means of detecting mutations in phytoplasma DNA sequences (Zong & Hiruki, 1994; Ceranic‐Zagorac & Hiruki, 1996; Cousin et al ., 1998; Wang & Hiruki, 1999; Wang & Hiruki, 2000) – it is simple to perform, and can yield a good estimation of phylogenetic distance (Delwart et al ., 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, heteroduplex mobilities are proportional to the degree of genetic distance between the two DNA strands (Delwart et al., 1995). Hence, this method has been used for identification, phylogenetic and epidemiological studies of several organisms including viruses (Delwart et al., 1993; Lin et al., 2000), phytoplasma (Zhong and Hiruki, 1994; Cousin et al., 1998), protozoan parasites (Leoni et al., 2002), bacteria (Jensen and Hubner, 1996; Garrec et al., 2003) and fungi (Kumeda and Asao, 2001; Ramos et al., 2001, 2006).…”
Section: Introductionmentioning
confidence: 99%